Analysis of the influencing factors in the long-term survival of esophageal cancer - Rui, Wang; Li, Congcong; Da, Qin; Yue, Yang; Jing, Li; Ruirui, Guo; Youbin, Cui; Lu, Tianyu; Li, Bo (Frontiers in Oncology, 2024)
Background: To analyze the prognosis and diagnostic value of relevant hematological indexes on the survival status of patients with esophageal squamous cell carcinoma after radical surgery. Methods: This study included 206 patients with esophageal cancer who underwent surgical R0 resection. The data, including the basic information, preoperative blood routine, albumin, fibrinogen, surgery-related information, postoperative pathology, and overall survival, of the patients were compared. Results: The survival and death groups showed a significant difference in overall survival (OS), the degree of differentiation, depth of infiltration, pathological stage, vascular infiltration, nerve infiltration, fibrinogen, white blood cell, neutrophils, platelet, and platelet hematocrit (P<0.05). Tumor located in the middle thorax, larger lesion length, deeper invasion, later pathological stage, vascular infiltration, nerve infiltration, lymph node metastasis, cardiovascular disease, and higher smoking grade were risk factors for poor prognosis of esophageal squamous cell carcinoma (ESCC) (P<0.05). Cardiovascular disease, lower differentiation, tumor located in the middle thorax, and nerve infiltration were independent risk factors for the reduction of survival time of patients with ESCC (P<0.05). Conclusions: History of cardiovascular disease, tumor located in the middle chest, poorly differentiated esophageal squamous cell carcinoma, visible nerve cancer invasion, hematocrit (HCT), mean erythrocyte hemoglobin concentration (MCHC), and hemoglobin (HB) are independent risk factors for the long-term survival of patients with ESCC.